Identification of CHRNB4 as a Diagnostic/Prognostic Indicator and Therapeutic Target in Human Esophageal Squamous Cell Carcinoma - Li, Nan; Liu, Kaisheng; Dong, Shaowei; Ou, Ling; Li, Jieling; Lai, Minshan; Wang, Yue; Bao, Yucheng; Shi, Huijie; Wang, Xiao; Wang, Shaoxiang (Frontiers in Oncology, 2020)
Esophageal squamous cell carcinoma (ESCC) is one of the most aggressive malignant tumors and there is a lack of biomarkers for ESCC diagnosis and prognosis. Family subunits of cholinergic nicotinic receptor genes (CHRNs) are involved in smoking behavior and tumor cell proliferation. Previous researches have shown similar molecular features and pathogenic mechanisms among ESCC, head and neck squamous cell carcinoma (HNSC), and lung squamous cell carcinoma (LUSC). Using edgeR, three mutual differentially expressed genes of CHRNs were found to be significantly upregulated at the mRNA level in ESCC, LUSC, and HNSC compared to matched normal tissues. Kaplan–Meier survival analysis showed that high expression of CHRNB4 was associated with unfavorable prognosis in ESCC and HNSC. The specific expression analysis revealed that CHRNB4 is highly expressed selectively in squamous cell carcinomas compared to adenocarcinoma. Cox proportional hazards regression analysis was performed to find that just the single gene CHRNB4 has enough independent prognostic ability, with the area under curve surpassing the tumor-node-metastasis (TNM) staging-based model, the most commonly used model in clinical application in ESCC. In addition, an effective prognostic nomogram was established combining the TNM stage, gender of patients, and expression of CHRNB4 for ESCC patients, revealing an excellent prognostic ability when compared to the model of CHRNB4 alone or TNM. Gene Set Enrichment Analysis results suggested that the expression of CHRNB4 was associated with cancer-related pathways, such as the mTOR pathway. Cell Counting Kit-8, cloning formation assay, and western blot proved that CHRNB4 knockdown can inhibit the proliferation of ESCC cells via the Akt/mTOR and ERK1/2/mTOR pathways, which might facilitate the prolonged survival of patients. Furthermore, we conducted structure-based molecular docking, and potential modulators against CHRNB4 were screened from FDA approved drugs. These findings suggested that CHRNB4 specifically expressed in SCCs, and may serve as a promising biomarker for diagnosis and prognosis prediction, and it can even become a therapeutic target of ESCC patients.